Surface Wrinkled Microsphere Enhanced Irregular Wound Healing Through Synergistic Hygroscopicity, Reversible Wet‐Adhesion and Antibacterial Properties - Zhan Xu; Yuqian Cui; Weiguo Tian; Feifei Sun; Jun Zhang (Small Science, 2024)
Rapid and effective healing of irregular wounds caused by burns, lacerations, and blast injuries remains a persistent challenge in wound care. Hydrogel microsphere dressings that can adaptively fill and adhere to the wounds without external force are desired to treat irregular wounds, providing an external barrier and accelerating healing. Herein, we created multifunctional cellulose‐based surface‐wrinkled microspheres with antioxidant, antibacterial, hygroscopicity, wet‐adhesion and shape‐adaptive capabilities to relieve inflammation, bacteria and excess exudate situations in healing irregular wounds. This dressing rapidly adsorbs exudate and reversibly adheres wetly to the wounds upon being filled, effectively inhibiting bacterial infection and reducing the flooded exudate to accelerate wound healing. Polydopamine (PDA) provides catechol‐based tissue bioadhesion to microspheres through π–π stacking or hydrogen bond interaction, and also establishes a bond bridge with an antimicrobial component (thymol), which not only enables the microspheres to stably adhere to the wound to maintain hygroscopicity, but also improves the release of the introduced antimicrobial component (thymol). In vivo assays, as well as histopathological and immunofluorescence studies have shown that multifunctional cellulose‐based microspheres have excellent pro‐healing abilities and are promising candidates for dehumidification and healing of irregular wound in clinical applications.